La Evasión Tributaria en los comerciantes de verduras ubicados en los mercados de la Provincia de San Martín – año 2013 - Pinedo Paredes, Henry (2014)
used. The research results indicate that a sample of 129 traders vegetable markets located in the province of San Martín Year 2013, the monthly sales volume of undeclared or omitted is S /.4'051,000.00, this amount to determine the levels of tax evasion is high, consisting of 76 informal traders representing 59% whose total sales are not declared to the SUNAT, intermediate comprised of 50 formal traders representing 39% turn these traders ignored some sales because they do not declare their income to the administrative authority and the low level formed by three traders who represent 2% of whose sales are declared in full to the sanctioning body. The conclusion of this study indicates that among the main causes of tax evasion was found that vegetable merchants are not adequate tax culture in the development of their activities, are not in accordance with current tax legislation because they consider it too complex in turn believe that taxes collected by the state through its collection agency (SUNAT) are excessive, it is not consistent with reality and are not equitable